Human cloning: considerations regarding international documents - Bompiani, Adriano (Medicina e Morale, 1998)
The Author analyses the various international documents, that have recently been prepared, regarding cloning the human being. There is a basic uniformity in condemning the process of creation in order to reproduce a human being that, because of cloning, has the same nuclear genetic patrimony as another person, whether alive or dead. The criticism of this aim is ethically motivated by the offence to human dignity and to man's fundamental rights that this model of cloning expresses. Therapeutic cloning, which aims to prevent the transmission of mitochondrial diseases, is not included in the international regulations proposed up to now (European Council, UNESCO). While the UNESCO has adopted a rather ambiguous text, the European Council has expressly prohibited cloning the human being for a nuclear transfer. New concerns are also appearing regarding the meaning to be given to the expression human being, which is to be reserved to the national law of each European country. If, in the interpretation, the denomination of human being were attributed to the implanted embryo, the pre-implantation phase (considered by some as "pre-embryonic") would not be included in the prohibition of cloning for experimentation, or to create possible therapeutic means.